Manipulating the Stacking of Triplet Chromophores in the Crystal Form for Ultralong Organic Phosphorescence. Issue 40 (28th August 2019) - Gan, Nan; Wang, Xuan; Ma, Huili; Lv, Anqi; Wang, He; Wang, Qian; Gu, Mingxing; Cai, Suzhi; Zhang, Yanyun; Fu, Lishun; Zhang, Meng; Dong, Chaomin; et al.
Abstract: Provided here is evidence showing that the stacking between triplet chromophores plays a critical role in ultralong organic phosphorescence (UOP) generation within a crystal. By varying the structure of a functional unit, and different on‐off UOP behavior was observed for each structure. Remarkably, 24CPhCz, having the strongest intermolecular interaction between carbazole units exhibited the most impressive UOP with a long lifetime of 1.06 s and a phosphorescence quantum yield of 2.5 %. 34CPhCz showed dual‐emission UOP and thermally activated delayed fluorescence (TADF) with a moderately decreased phosphorescence lifetime of 770 ms, while 35CPhCz only displayed TADF owing to the absence of strong electronic coupling between triplet chromophores. This study provides an explanation for UOP generation in crystal and new guidelines for obtaining UOP materials. Abstract : Ultralong organic phosphorescence (UOP) can be controlled by manipulating the stacking of the triplet chromophores within a crystal form. The stronger the interaction between carbazole chromophores the more favorable the generation of UOP (see 24CPhCz and 34CPhCz in the picture). Weaker interactions between the triplet chromophores, accompanied by strong interactions between benzene units resulted in the disappearance of the UOP and appearance of thermally activated delayed fluorescence (TADF; 35CPhCz).